Brodie syndrome in early mixed dentition treated with adhesive removable appliance A case report - Soldevilla Galarza, Luciano (2008)
We reported a clinical case of crossed vestibular posterior bilateral bite identified as the Brodie bite that compromises the use of a bonded removable appliance with reverse screw action in the upper maxillary and the use of lower Bihelix. The purpose of modifications of the design permits the expansion appliance to be used in reverse mode mainly in the correction of the Brodie bite in the early mixed dentition. The goals of the treatment were to achieve the correct interception between the teeth of the upper and lower jawbone, to eliminate the mandibular entrapment and the correction of the crossed vestibular posterior bilateral bite.